PENGARUH KEBERADAAN PERGURUAN TINGGI TERHADAP PERUBAHAN MORFOLOGI KAWASAN SEKITARNYA - Atik Munggiarti; Imam Buchori (Geoplanning: Journal of Geomatics and Planning, 2015)
This research aims to analyze the morphology changes of the area surrounding Jenderal Sudirman University (Unsoed), Purwokerto. It is important because according to the City Detail Spatial Plan (RDTR)  of Purwokerto 2014-2034 Unsoed is planned as a center of educational services. It will increase the trade and service activities supporting the educational  and residential activities. So, it would increase the intensity of activities that would indirectly affect the physical changes of the surrounding area. This research has used GIS-based spatial analysis to determine the land cover or landuse change, area of land conversion, change in building density, and descriptive analysis to identify the morphology and growth pattern of the area. In addition, the influence of the university on the morphological changes in the surrounding area is analyzed. The results can identify that Unsoed has been influencing significantly (more than 80%) on the changes in the morphology of the area. It can be proven by the following findings: (1) The increasing built-up area surrounding the university, especially at a radius of 500 m, which is 18.3% from the year 2003 to 2013. (2) The building density has increased by 4.93% per year. (3) The growing activities tend to cluster around the neighborhood streets and along the primary collector street, which indicates the linear growth pattern, while in some parts, such as in Grendeng and Karangwangkal villages, the pattern is octopus form. (4) The proximity to Unsoed has become an important reason (81.2%) for the establishment of buildings within the radius of 500 meters from the campus. (5) The influence of Unsoed is much greater in the villages of Grendeng and Karangwangkal where the campus is located than that in the villages outside the campus location, i.e. Bancarkembar, Sumampir and Pabuwaran Villages. © 2015 GJGP UNDIP. All rights reserved.